2008
DOI: 10.1002/mana.200510597
|View full text |Cite
|
Sign up to set email alerts
|

An extraordinary origami curve

Abstract: We study the origami W defined by the quaternion group of order 8 and its Teichmüller curve C(W ) in the moduli space M3. We prove that W has Veech group SL2(Z), determine the equation of the family over C(W ) and find several further properties. As main result we obtain infinitely many origami curves in M3 that intersect C(W ). We present a combinatorial description of these origamis.Origami curves are certain special Teichmüller curves in some moduli space of curves. They are obtained from an unramified cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 16 publications
1
66
0
3
Order By: Relevance
“…Moreover we will make some remarks aboutḠ 4 and E 4 . We obtain due to [24], Proposition 9 and the notations of [24], Section 2: The involutions of E 4 are given by (αβ) ν , α ζ , β ς and γ κ for ν = 2, ζ 2 = 1 − λ, ς 2 = 1 − 1 λ and κ 2 = λ. The group E 4 has a subgroup isomorphic to the quarternion group given by (αβ) ν , α ζ , β ς and γ κ for ν = 0, 2, ζ 2 = −1 + λ, ς 2 = −1 + 1 λ and κ 2 = −λ.…”
Section: The Extended Automorphism Group Of the Degree 4 Examplementioning
confidence: 99%
“…Moreover we will make some remarks aboutḠ 4 and E 4 . We obtain due to [24], Proposition 9 and the notations of [24], Section 2: The involutions of E 4 are given by (αβ) ν , α ζ , β ς and γ κ for ν = 2, ζ 2 = 1 − λ, ς 2 = 1 − 1 λ and κ 2 = λ. The group E 4 has a subgroup isomorphic to the quarternion group given by (αβ) ν , α ζ , β ς and γ κ for ν = 0, 2, ζ 2 = −1 + λ, ς 2 = −1 + 1 λ and κ 2 = −λ.…”
Section: The Extended Automorphism Group Of the Degree 4 Examplementioning
confidence: 99%
“…Gutkin and Judge [27] showed that every arithmetic surface is a cover of a torus, with possible ramification above one point. These so-called square-tiled surfaces (also known as origami) are dense in ΩM g , and provide key specific examples in the theory [25,29]. Schmithüsen [71] gave an algorithm for computing the Veech group in this setting.…”
Section: Teichmüller Curves Exist But Are Rarementioning
confidence: 99%
“…Möller and Viehweg [63] characterize all Kobayashi curves in A g , showing rigidity. Möller [60] shows that for g = 5 there are exactly two Teichmüller curves (those given in [25,29]), that are simultaneously Shimura curves.…”
Section: Kobayashi Curvesmentioning
confidence: 99%
“…Recall from (18) in Chapter 3 that a base of open neighbourhoods of (X ∞ , f ∞ ) is given by the open sets…”
Section: Convergencementioning
confidence: 99%
“…Using the description of origamis by gluing squares it is not difficult to see that there are, for any g ≥ 2, infinitely many Teichmüller curves in M g that come from origamis. In genus 3 there is even an explicit example of an origami curve that is intersected by infinitely many others, see [18].…”
Section: Introductionmentioning
confidence: 99%